Bone structural data for the Denver longitudinal growth study. Issue 3 (26th April 2022) - Ruff, Christopher B.
Abstract: The Denver Longitudinal Growth Study is one of the most comprehensive longitudinal studies of growth carried out to date. Measurements of long bone lengths, cross‐sectional diaphyseal properties, and articular breadths were taken from archived radiographs of 20 study subjects measured at an average of 36 time points from early infancy to late adolescence. Anthropometric dimensions for these individuals were also obtained from study archives. These data are now available in an online data set: 10.5061/dryad.xsj3tx9gq .